Imagining a Post-Pandemic Reality through an Arts-based Methodological Framework - Janes, Hayley; Berry, Adrian; Lyonblum, Ely; Risk, Laura; Niknafs, Nasim (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2023)
The COVID-19 pandemic exacerbated the precarity of artistic livelihoods across the arts and culture sector. With efforts to repair past harms and reimagine more equitable futures comes the need to center the lived experiences of artists in research and policy development. Sustainable pARTnerships: Collaboration and Reciprocity in Creative Cities is a participatory arts-based research initiative that brings together the cultural and academic sectors to jointly imagine futures in which artists can thrive. As part of this initiative, five researchers and five commissioned Toronto-based artists representative of a range of disciplines collaboratively documented challenges and potential next steps. This collaboration was framed with the methodologies of crystallization, crystal-scaping, and photovoice. Our objective is to artfully integrate artistic voices into the practice of knowledge creation and map out policy pathways for institutions and the community to create longer-term relationships built on equity and reciprocity. The visibility of local artists’ pandemic experience targets a broad public, including arts training institutes, policymakers, and academics and heightens the call for connection, conversation, and change.